2022
DOI: 10.2147/ijn.s380598
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin-Loaded High-Density Lipoprotein Exerts Promising Anti-Ovarian Cancer Effects by Inhibiting Epithelial–Mesenchymal Transition

Abstract: Background Effective treatments for ovarian cancer remain elusive, and survival rates have long been considered grim. Ovarian cancer stem cells (OCSCs) and epithelial–mesenchymal transition (EMT) are associated with cancer progression and metastasis, as well as drug resistance and eventual treatment failure. Salinomycin (Sal) has an extensive effect on a variety of cancer stem cells (CSCs); however, its poor water solubility and toxicity to healthy tissues at high doses limit further research into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Constructing a carrier mimicking high-density lipoprotein (HDL) in combination with salinomycin (S-HDL) has been demonstrated to have potent anticancer effects in OC as it inhibits translation of the CSCs proteins c-Myc, NANOG, OCT4 and SOX2 which are associated with chemoresistance and OC recurrence ( 34 ). The authors of the investigation on the effects of metformin and salinomycin consider that these two drugs will be an effective future therapy in improving survival and preventing recurrence of OC.…”
Section: Cancer Stem Cells (Cscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Constructing a carrier mimicking high-density lipoprotein (HDL) in combination with salinomycin (S-HDL) has been demonstrated to have potent anticancer effects in OC as it inhibits translation of the CSCs proteins c-Myc, NANOG, OCT4 and SOX2 which are associated with chemoresistance and OC recurrence ( 34 ). The authors of the investigation on the effects of metformin and salinomycin consider that these two drugs will be an effective future therapy in improving survival and preventing recurrence of OC.…”
Section: Cancer Stem Cells (Cscs)mentioning
confidence: 99%
“…Salinomycin, an ionophore antibiotic isolated from Streptomyces albus, selectively eradicates CSCs (32)(33)(34). Previous studies on OC cell lines (OVCAR3) have revealed an inhibitory effect of salinomycin in combination with paclitaxel on CD44(+) and CD117(+) expression (32).…”
Section: Cancer Stem Cells (Cscs)mentioning
confidence: 99%
“…Salinomycin has also been shown to be a selective inhibitor of BCSC and OCSC. It induces apoptosis in OCSC and selectively kills BCSC while reducing tumor growth and EMT [ 416 , 417 , 458 ]. However, its disadvantage is poor solubility in water and poor bioavailability, which can be remedied by conjugation with CD133-targeted nanoparticles [ 459 ].…”
Section: Csc-targeted Therapiesmentioning
confidence: 99%
“…OC cell line (CD133+ population), normal ovarian epithelial line, xenografts Downregulation of stemness markers (MYCN, NANOG, OCT4, SOX2) in vitro and in vivo, induction of apoptosis [417].…”
Section: Salinomycin-hdlmentioning
confidence: 99%
“…SAL has the ability to promote differentiation of cancer cells early on in development, and it can reprogram epithelial growth that undergoes epithelial mesenchymal transition (EMT) and leads to the upregulation and expression of certain genes, such as mammary epithelial differentiation [42,64]. Based on these findings, SAL can eliminate CSCs through multiple mechanisms of action known from the literature (Table 1).…”
Section: Differentiation Of Cscs and Sal Bioactivitymentioning
confidence: 99%